2004
DOI: 10.1038/nrm1435
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis: signalling the way forward

Abstract: During random locomotion, human neutrophils and Dictyostelium discoideum amoebae repeatedly extend and retract cytoplasmic processes. During directed cell migration--chemotaxis--these pseudopodia form predominantly at the leading edge in response to the local accumulation of certain signalling molecules. Concurrent changes in actin and myosin enable the cell to move towards the stimulus. Recent studies are beginning to identify an intricate network of signalling molecules that mediate these processes, and how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
586
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 650 publications
(594 citation statements)
references
References 106 publications
7
586
0
1
Order By: Relevance
“…The GPCR activation triggers actin cytoskeleton reorganization to form lamellipodia, the flattened F-actin-rich leading edge of migrating cells, which is a critical process of cancer cell metastasis (Van Haastert and Devreotes, 2004). We found that treatment with pristimerin significantly reduced the chemotactic reagentmediated lamellipodia formation in breast cancer cells in vitro.…”
Section: Discussionmentioning
confidence: 77%
“…The GPCR activation triggers actin cytoskeleton reorganization to form lamellipodia, the flattened F-actin-rich leading edge of migrating cells, which is a critical process of cancer cell metastasis (Van Haastert and Devreotes, 2004). We found that treatment with pristimerin significantly reduced the chemotactic reagentmediated lamellipodia formation in breast cancer cells in vitro.…”
Section: Discussionmentioning
confidence: 77%
“…Although a number of intracellular signalling pathways involved in the polarization and directional migration of cells have been characterized (Jones, 2000;Weiner, 2002;Van Haastert and Devreotes, 2004), relatively little is known as to how these signal transduction components are coupled to the transmembrane receptors that sense the chemotactic gradient. Previously, we have demonstrated that the CD44 S291A mutant blocks the chemotactic migration of CD44-expressing MDA-MB-435 breast cancer cells up a PMA gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotaxis is essential for a variety of physiological processes in mammals as well as for the survival of lower eukaryotes. The mechanisms that regulate the directed migration of neutrophils and Dictyostelium discoideum have been extensively studied previously (van Haastert and Devreotes, 2004;Bagorda et al, 2006;Friedl and Weigelin, 2008;Stephens et al, 2008). One particular challenge of these fast-moving cells is to maintain the ability to respond sensitively and rapidly to an attractant signal.…”
Section: Introductionmentioning
confidence: 99%